Motor dysfunction as a primary symptom predicts poor outcome: multicenter study of glioma symptoms - Kivioja, Tomi (Switzerland, 2025)
Background and objectives: The objectives of this study were to investigate the prognostic value of primary symptoms and leading symptoms in adult patients with diffuse infiltrating glioma and to provide a clinical perspective for evaluating survival.
Methods: This study included a retrospective cohort from two tertiary university hospitals (n = 604, 2006-2013, Tampere University Hospital and Turku University Hospital) and a prospective cohort (n = 156, 2014-2018, Tampere University Hospital). Preoperative symptoms were divided into primary and leading symptoms. Results were validated with the newer WHO 2021 classification criteria.
Results: The most common primary symptoms were epileptic seizure (30.8% retrospective, 28.2% prospective), cognitive disorder (13.2% retrospective, 16.0% prospective), headache (8.6% retrospective, 12.8% prospective), and motor paresis (7.0% retrospective, 7.1% prospective). Symptoms that predicted better survival were epileptic seizure and visual or other sense-affecting symptom in the retrospective cohort and epileptic seizure and headache in the prospective cohort. Predictors of poor survival were cognitive disorder, motor dysfunction, sensory symptom, tumor hemorrhage, speech disorder and dizziness in the retrospective cohort and cognitive disorder, motor dysfunction, sensory symptom, and dizziness in the prospective cohort. Motor dysfunction served as an independent predictor of survival in a multivariate model (OR = 1.636).
Conclusion: Primary and leading symptoms in diffuse gliomas are associated with prognoses in retrospective and prospective settings. Motor paresis was an independent prognostic factor for poor survival in multivariate analysis for grade 2-4 diffuse gliomas, especially in glioblastomas.